Percutaneous Coronary Intervention after Fibrinolysis for ST-Segment Elevation Myocardial Infarction Patients: An Updated Systematic Review and Meta-Analysis. - Feng Liu; Qinglong Guo; Guoqiang Xie; Han Zhang; Yaxi Wu; Lixia Yang (PLoS ONE)
Background Percutaneous coronary intervention (PCI), fibrinolysis and the combination of both methods are current therapeutic options for patients with ST-segment elevation myocardial infarction (STEMI). Methods We searched PubMed, EMBASE, Google scholar and Cochrane Controlled Trials Register for randomized controlled trials (RCTs) evaluating the efficacy and safety of PCI after fibrinolysis within 24 hours, which was compared with primary PCI alone and ischemia-guided or delayed PCI. Meta-analysis was conducted using Review Manager 5.30 following the methods described by the Cochrane library. Results A total of 16 studies including 10,034 patients were enrolled. As compared with primary PCI alone group, the short-term mortality (5.8% vs 4.5%, RR 1.29, 95% confidence interval [CI] 1.00-1.65) and re-infarction rate (4.1% vs 2.7%, RR 1.46, 95%CI 1.05-2.03) were higher in the immediate PCI group (median/mean time ≤ 2 h after fibrinolysis). However, the short-term mortality and re-infarction rate showed no statistically significant differences in the early PCI group (2-24 hours after fibrinolysis). The rate of major bleeding events was higher both in the immediate PCI (6.3% vs 4.4%, RR 1.43, 95%CI 1.11-1.85) and the early PCI group (6.4% vs 4.4%, RR 1.46, 95%CI 1.03-2.06) as compared with primary PCI alone group. As compared with ischemia-guided or delayed PCI, early PCI was associated with significantly reduced re-infarction (2.4% vs 4.0%, RR 0.61, 95%CI 0.41-0.92) and recurrent ischemia (1.5% vs 5.3%, RR 0.29, 95%CI 0.12-0.70) at short-term. And the reduced re-infarction rate was also observed at long-term. Conclusions Early PCI after fibrinolysis, with a relatively broader time for PCI preparation, can bring the similar effects with primary PCI alone and is better than ischemia-guided or delayed PCI in STEMI patients with symptom onset < 12 h who cannot receive timely PCI. However, immediate PCI after fibrinolysis is detrimental.